Pengembangan Media Evaluasi Pembelajaran Berbasis Aplikasi Game Kahoot pada Materi Reaksi Redoks untuk Siswa Kelas X SMAN 5 Mataram - Nabila Nurhaliza; Syarifa Wahidah Al Idrus; Sunniarti Ariani (Lembaga Yasin AlSys, 2026)
The development of digital technology-based learning evaluation media is needed to support more interactive chemistry learning, particularly on the topic of Redox Reactions, which is abstract and has the potential to cause conceptual difficulties for students. This study aims to describe the process of developing learning evaluation media based on the Kahoot game application on the topic of Redox Reactions and to determine its level of feasibility and practicality for Grade X students at SMAN 5 Mataram. This study used a Research and Development method with the 4D model, which includes the Define, Design, Develop, and Disseminate stages. The study was conducted at SMAN 5 Mataram by involving expert validators, chemistry subject teachers, and Grade X students as research subjects. Data were collected through validation sheets and practicality response questionnaires, then analyzed using quantitative descriptive techniques to measure material feasibility, media feasibility, and user responses in the field. The results showed that the developed Kahoot game media met the feasibility criteria, with an average validation percentage of 93.13% in the very valid category. The practicality level of the media based on teacher responses obtained a score of 85%, while student responses obtained a score of 86.68%, and both were included in the very practical category. The conclusion of this study affirms that Kahoot game-based learning evaluation media on the topic of Redox Reactions has met the standards of validity and practicality for use in Grade X chemistry learning. These findings imply the use of interactive digital evaluation media as a supporting tool for innovative learning, while also encouraging the optimization of feedback features in the final product to strengthen independent conceptual understanding and directly minimize students’ misconceptions.